The destabilisation of the German electricity industry (1998-2015): Application and extension of a multi-dimensional framework - Gregor Kungl; Frank W. Geels (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2016)
This article aims to explain the rapid destabilisation of the German electricity industry between 1998 and 2015. The longitudinal case study uses analytical categories from a multi-dimensional framework, which emphasises the importance of external pressures on the industry (both techno-economic and socio-political) and firm-level response strategies (technical innovation, economic positioning, cultural framing, corporate political strategies). We also extend the framework by investigating the effects of different kinds and temporal sequence of external pressures, and the role of industry heterogeneity in shaping response strategies. The case study uses a wide range of primary sources (interviews with high-level managers, press releases, annual reports, newspapers) and secondary sources (quantitative statistics, academic articles, books) to develop a comprehensive, multi-dimensional explanation of the destabilisation process. – – Dieser Artikel will die rapide Destabilisierung der deutschen Elektrizitätsindustrie im Zeitraum zwischen 1998 und 2015 erklären. Hierfür wird eine multidimensionale Forschungsheuristik - das Triple Embeddedness Framework (Geels 2014) - angelegt, welches die Bedeutung von externen (sozio-politischen und ökonomischen) Veränderungen sowie von Anpassungsstrategien der Unternehmen (technologische Innovationen, Öffentlichkeitsarbeit oder politische Strategien) gleichermaßen in Rechnung stellt. Wir erweitern dieses Framework, indem wir die Rolle verschiedener Arten von externen Veränderungen sowie deren temporale Sequenzen berücksichtigen und außerdem die Rolle von Heterogenität innerhalb einer Industrie untersuchen. Die Fallstudie greift auf einen breiten Fundus an primären Datenquellen (Interviews mit Managern, Pressemitteilungen, Geschäftsberichte, Zeitungsartikel) sowie Sekundärquellen (quantitative Statistiken, wissenschaftliche Artikel und Bücher) zurück, um so eine umfassende, multi-dimensionale Analyse des Destabilisierungsprozesses zu bieten.
Keywords: 300